PENGARUH KETERSEDIAAN FASILITAS, ATRAKSI WISATA TERHADAP JUMLAH WISATAWAN, PENDAPATAN MASYARAKAT DI PURA TIRTA TAMAN MUMBUL - Putra, I Putu Agus Nopiatmaja; Dewi, Made Heny Urmila (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The development of spiritual tourism Tirta Taman Mumbul Temple has become a visiting trend to conduct spiritual tourism activities. The purpose this study 1) analyze effect of availability facilities and tourist attractions on number tourist visits in Taman Mumbul Temple, 2) analyze influence of availability facilities, tourist attractions, and number of tourist visits to income people working in Taman Mumbul Temple, 3) analyze influence of number of tourist visits mediating availability facilities, and availability of tourist attractions on income of people working in Taman Mumbul Temple. Samples taken 82 people with saturated samplings, used  path analysis thecnic. The results showed that the direct effect of the availability of facilities and tourist attractions had a positive and significant effect on the number of tourists. Direct influence variable Availability of facilities Number of tourists, tourist attractions have a positive and significant effect on community income. The indirect effect of the availability of facilities through the number of tourists has a positive and significant effect on people's income. The indirect effect of tourist attractions through the number of tourists has a positive and significant effect on people's income.   Keywords: facilities, availability of attractions, number of tourist visits, community income.